Hepatotoxicity of antipsychotics: an exploratory pharmacoepidemiologic and pharmacodynamic study integrating FAERS data and in vitro receptor-binding affinities - Zeiss, René; Schönfeldt-Lecuona, Carlos; Connemann, Bernhard J.; Hafner, Susanne; Gahr, Maximilian (Frontiers in Psychiatry, 2024)
Introduction Antipsychotic psychopharmacotherapy is associated with the risk of drug-induced liver injury (DILI). However, understanding specific risk factors remains challenging due to limited data. This study investigates the relationship between receptor binding affinities and occupancies of antipsychotics and their associated hepatotoxic risks. Methods A disproportionality analysis with calculation of the Reporting Odds Ratio (ROR) and the Information Component (IC) was conducted using data from the FDA Adverse Event Reporting System (FAERS) to identify signals related to the Standardised MedDRA Query “drug-related hepatic disorders”, which served as a proxy for drug-induced hepatotoxicity. This was followed by a pharmacoepidemiologic-pharmacodynamic approach to investigate the relationship between the ROR and substance-related receptor binding affinities and occupancy, which was estimated based on in vitro receptor-binding profiles. Results Significant signals were identified for several antipsychotics, including chlorpromazine, loxapine, olanzapine, and quetiapine, with chlorpromazine and loxapine showing the highest RORs for DILI. Gender-specific analysis revealed a higher frequency of signals in female patients. Statistically significant negative correlations were identified between the ROR for drug-related hepatic disorders and the affinity for serotonin receptor 5-HT1A (r (17) = -0.68, p = 0.0012), while a positive correlation was observed for cholinergic receptors (r (17) = 0.46, p = 0.048). No significant correlations were found related to other receptors or drug properties. Conclusion Our findings suggest that the serotonin and probably the cholinergic system may play a role in the development of DILI related to antipsychotic medications. The identification of antipsychotics with a higher association with DILI, such as chlorpromazine, underscores the need for careful monitoring in clinical practice. However, our findings need further longitudinal studies to confirm causality. A better understanding of the associations may inform clinical decision-making, particularly in patients with an increased susceptibility to liver damage.